Improving the Poetry Writing Skills of Grade VIII Students of SMP IT Al-Fateeh Semarang Using Wordwall Media - Shohib, Ahmad Mujib; Arsanti, Meilan; Azizah, Aida (Jurnal Penelitian Pendidikan, 2025)
The implementation of student learning activities is more attracted to media involving gadgets. Students who like games on gadgets sometimes make them prefer similar activities. The purpose of this study is to describe wordwall media in poetry writing skills for class VIII in order to test the increase in students' understanding of poetry writing material. The method used is PTK (Classroom Action Research) with qualitative descriptive techniques. The results of this study can be used as a fun learning media to improve students' understanding of poetry writing material for class VIII using wordwall media. The process of learning to write poetry using wordwall media is carried out well and smoothly, students can understand the material of writing poetry well. So there is an increase from pre-cycle to cycle I to cycle II. The percentage of classical completeness criteria increases from pre-cycle to cycle I to cycle II for class VIII B from 27% to 60% to 80% and for class VIII C from 31% to 54% to 85%.